2012
DOI: 10.1364/oe.20.022490
|View full text |Cite
|
Sign up to set email alerts
|

Structural factors impacting carrier transport and electroluminescence from Si nanocluster-sensitized Er ions

Abstract: Abstract:We present an analysis of factors influencing carrier transport and electroluminescence (EL) at 1.5 µm from erbium-doped silicon-rich silica (SiO x ) layers. The effects of both the active layer thickness and the Siexcess content on the electrical excitation of erbium are studied. We demonstrate that when the thickness is decreased from a few hundred to tens of nanometers the conductivity is greatly enhanced. Carrier transport is well described in all cases by a Poole-Frenkel mechanism, while the thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…While this initial demonstration focused on all-optical modulation, switching of VO 2 could also be produced by electrically triggering the IMT 24 25 (see Supplementary Note 2 for discussion of switching energy). Combined with electroluminescent devices 26 27 , all-electrical direct modulation of emission could be obtained. The presented concept is not limited to Er 3+ ions and VO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…While this initial demonstration focused on all-optical modulation, switching of VO 2 could also be produced by electrically triggering the IMT 24 25 (see Supplementary Note 2 for discussion of switching energy). Combined with electroluminescent devices 26 27 , all-electrical direct modulation of emission could be obtained. The presented concept is not limited to Er 3+ ions and VO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Basically, there are four main mechanisms known to contribute in the carrier transport through a Si-rich oxide layer, including the direct tunneling, Fowler Nordheim tunneling (F-N), Poole-Frenkel (P-F) and the trap-assisted tunneling (TAT) [33][34][35][36][37]. It has been found that the TAT conduction mechanism predominates in our SRO 30 -based LECs, where the trap energy (ϕ t ) was estimated at about 1.99 eV [28].…”
Section: Electrical Characteristicsmentioning
confidence: 99%
“…1 For decades, spontaneous emission from Er 3+ ions has been investigated for applications in integrated optics, [2][3][4][5][6] including recent work exploring enhanced Er 3+ emission within optical nanostructures as the basis for chip-scale devices. [7][8][9][10][11][12][13] Spontaneous emission from Er 3+ also serves as the basis for the upconverting phosphors used in silicon-based near-infrared cameras, 14 and recent work has shown how upconverting erbium-doped nanoparticles can serve as low-background, photo-stable light sources for microscopy and bio-imaging. [15][16][17] In addition to its technological importance, Er 3+ light emission has been the subject of numerous scientific studies, including canonical experiments on the study of lightmatter interactions.…”
Section: Introductionmentioning
confidence: 99%